Detection and Localization of Abnormalities in Surveillance Video Using Timerider-Based Neural Network. (19th March 2021) - Veluchamy, S; Karlmarx, L R; Mahesh, K Michael
Abstract: Automatic anomaly detection in surveillance videos is a trending research domain, which assures the detection of the anomalies effectively, relieves the time-consumed by the manual interpretation methods without the requirement of the domain knowledge about the anomalous object. Accordingly, this research work proposes an effective anomaly detection approach, named, TimeRide Neural network (TimeRideNN), by modifying the standard RideNN using the Taylor series such that an extra group of rider, named as timerider, is included in the standard rider optimization algorithm. Initially, the face in the videos is subjected to face detection using the Viola Jones algorithm. Then, the object tracking is performed using the knocker and holoentropy-based Bhattacharya distance, which is a modification of the Bhattacharya distance using the knocker and holoentropy. After that, the features, such as object-level features and speed-level features of the objects, are extracted and the features are employed to the proposed TimeRideNN classifier, which declares the anomalous objects in the video. The experimentation of the proposed anomaly detection method is done using the UCSD dataset (Ped1), subway dataset and QMUL junction dataset, and the analysis is performed based on accuracy, sensitivity and specificity. The proposed TimeRideNN classifier obtains the accuracy, sensitivity and specificity of 0.9724, 0.9894 and 0.9691, respectively.